Hematologic and molecular identification of Anaplasma platys in domestic canine in Lima with clinic signs compatible with anaplasmosis - Tateishi T., Viviana (2015)
This study aimed to determine the presence ofAnaplasma platys in domestic dogs of Metropolitan Lima with clinic signs consistent with anaplasmosis by identifying inclusion bodies in platelets and through the Hemi-Nested PCR technique using peripheral blood samples. For this purpose, 144 samples were collected between January to December 2012. The results showed that 29.2% (42/144) were positive (thrombocytopenic individuals and presence ofinclusion bodies in platelets) and 12.5% (18/144) were suspicious (nonthrombocytopenic individuals and presence of inclusion bodies in platelets) by hematologic identification. Moreover, 1.4% (2/144) resulted positive to the Hemi-Nested PCR test. These results confirm the presence ofA. platys in domestic dogs in the country